Garlic Lowers Blood Pressure in Hypertensive Individuals, Regulates Serum Cholesterol, and Stimulates Immunity: An Updated Meta-analysis and Review - Ried, Karin (The Journal of nutrition, 2016)
Garlic has been shown to have cardiovascular protective and immunomodulatory properties. We updated a previous meta-analysis on the effect of garlic on blood pressure and reviewed the effect of garlic on cholesterol and immunity. We searched the Medline database for randomized controlled trials (RCTs) published between 1955 and December 2013 on the effect of garlic preparations on blood pressure. In addition, we reviewed the effect of garlic on cholesterol and immunity. Our updated meta-analysis on the effect of garlic on blood pressure, which included 20 trials with 970 participants, showed a mean ± SE decrease in systolic blood pressure (SBP) of 5.1 ± 2.2 mm Hg (P < 0.001) and a mean ± SE decrease in diastolic blood pressure (DBP) of 2.5 ± 1.6 mm Hg (P < 0.002) compared with placebo. Subgroup analysis of trials in hypertensive subjects (SBP/DBP ≥140/90 mm Hg) at baseline revealed a larger significant reduction in SBP of 8.7 ± 2.2 mm Hg (P < 0.001; n = 10) and in DBP of 6.1 ± 1.3 mm Hg (P < 0.001; n = 6). A previously published meta-analysis on the effect of garlic on blood lipids, which included 39 primary RCTs and 2300 adults treated for a minimum of 2 wk, suggested garlic to be effective in reducing total and LDL cholesterol by 10% if taken for >2 mo by individuals with slightly elevated concentrations [e.g., total cholesterol >200 mg/dL (>5.5 mmol/L)]. Garlic has immunomodulating effects by increasing macrophage activity, natural killer cells, and the production of T and B cells. Clinical trials have shown garlic to significantly reduce the number, duration, and severity of upper respiratory infections. Our review suggests that garlic supplements have the potential to lower blood pressure in hypertensive individuals, to regulate slightly elevated cholesterol concentrations, and to stimulate the immune system. Garlic supplements are highly tolerated and may be considered as a complementary treatment option for hypertension, slightly elevated cholesterol, and stimulation of immunity. Future long-term trials are needed to elucidate the effect of garlic on cardiovascular morbidity and mortality.